Gambaran Kesehatan Lingkungan Rumah pada Pasien Tuberkulosis Paru - Desy Indra Yani; Riani Pebrianti; Dadang Purnama (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the environmental health picture of TB patients in Kadungora District, Garut Regency. The method used is descriptive quantitative. The results of this study indicate a occupancy density of 56.3% which meets the requirements, unhealthy room ventilation is 18.8%, the humidity of an unhealthy patient's room is 43.8%, the temperature value in the respondent's house has a normal value of 18- 300C with a percentage of 100% and the lighting that is owned has a normal value when the lamp is turned on with a percentage of 95%. In conclusion, the density of occupancy in the homes of TB patients in the Kadungora area has densely populated houses. The room ventilation area that meets the requirements for TB patients is 26 rooms. Humidity in the house of a patient with TB in the Kadungora area that meets the requirements when the window door is opened in a room that meets the requirements of 21 rooms Keywords: Environmental Health, Home, Pulmonary Tuberculosis